Penguatan Konsep Berbasis Pertanian Berkelanjutan di Negara India sebagai Solusi Mengurangi Efek Gas Rumah Kaca (Literature Review) - Yudianto, Tri; Pramono, Edi; Rezaldi, Firman; Rahmad, Sukardi Sugeng; Yenny, Ratna Fitry; Gumilar, Roni; Trisnawati, Desi; Ginaris, Rifkarosita Putri; Suminar, Erni (Jurnal Agroteknologi (Agronu), 2025)
The conventional agricultural system that is applied tends to use chemicals such as pesticides, on the one hand, providing various positive impacts, including increasing productivity quickly, meeting food needs efficiently, and helping food insecurity as often occurs in India. Sustainable agricultural systems are aimed at reducing environmental damage, maintaining agricultural productivity, increasing farmers' income and improving the stability and quality of life of rural communities. Three big indicators that can be seen are that the environment is sustainable, the economy is improving (prosperous), and it is socially accepted by the farming community. Other negative impacts on conventional agricultural systems include decreasing soil quality, giving rise to new pests and diseases, environmentally friendly microorganisms becoming extinct, toxic chemicals threatening the condition of the biosphere in the food chain. The concept of organic farming that is applied ideally is based on optimal, balanced, efficient management of land, water and land, so that existing biodiversity is one of the external efforts to provide a positive impact. In writing this literature review, the sections that will be discussed include the application of conventional agricultural systems that occur in India, suggestions and improvements that can be implemented based on potential such as modeling greenhouse gas emissions from agriculture, GHG (Greenhouse Gas) mitigation from agriculture, absorption of element C in agricultural soil, conservation agriculture, reducing nitrous oxide emissions, economic implications of greenhouse gas mitigation, and the use of butterfly pea flower kombucha in agricultural aspects